1990
DOI: 10.1113/jphysiol.1990.sp018091
|View full text |Cite
|
Sign up to set email alerts
|

Increased airway reactivity in the guinea‐pig follows exposure to intravenous isoprenaline.

Abstract: 1. Intravenous infusion of (+/‐) isoprenaline (1‐100 micrograms kg‐1 h‐1) enhanced airway responses (resistance, RL; and compliance, Cdyn) to histamine (1.0‐1.8 micrograms kg‐1) and bombesin (100‐240 ng kg‐1), whereas airway responses to vagal stimulation remained unchanged. 2. Bilateral vagotomy before intravenous infusion of (+/‐)isoprenaline (100 micrograms kg‐1 h‐1) prevented development of airway hyperreactivity to histamine or bombesin, yet vagotomy after infusion of isoprenaline was without effect. 3. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 31 publications
3
24
2
Order By: Relevance
“…Our observations confirm the principal findings reported by Morley and co-workers Mazzoni et al, 1987;Sanjar et al, 1990;Morley et al, 1991) tivity in anaesthetized guinea-pigs. However, some of our results differ and require some discussion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations confirm the principal findings reported by Morley and co-workers Mazzoni et al, 1987;Sanjar et al, 1990;Morley et al, 1991) tivity in anaesthetized guinea-pigs. However, some of our results differ and require some discussion.…”
Section: Discussionsupporting
confidence: 93%
“…This is at variance with the observations of Sanjar et al (1990) who observed no enhancement. The difference can perhaps be explained by inspection of our Figure 6a.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…More recently, it has been established that acute in travenous infusion of (±)isoprenaline induces airway hyperreactivity in guinea pigs (7), and this effect has been shown to extend to p2-selective sympathomimetics such as (± )salbutamol (8). Acutely, this property of (± )salbuta mol is masked by the bronchodilator action of (-)salbuta mol, but following sustained infusion of (±)salbuta mol over several days, increased sensitivity of the airways can be demonstrated to antigen (9) and to airway spas mogens (10).…”
mentioning
confidence: 99%
“…Initial studies in that area begin in the late 1970s and have started by looking at the combined effect of spasmogens on different measures of lung function in animals (45,46,57,99,102,112,131,152,180,181,192,208,209,224,244), as well as in humans (49,68,97,101,110,156,158,194,202,240). Apart from an interactive synergism at the level of ASM contraction, many other factors can account for these in vivo interactive synergisms.…”
Section: Interactive Synergisms Between Spasmogensmentioning
confidence: 99%